2006
DOI: 10.22621/cfn.v120i3.321
|View full text |Cite
|
Sign up to set email alerts
|

Pack Size of Wolves, <em>Canis lupus</em>, on Caribou, <em>Rangifer tarandus</em>, Winter Ranges in Westcentral Alberta

Abstract: We studied pack size of Wolves (Canis lupus) on Woodland Caribou (Rangifer tarandus caribou) winter ranges in westcentral Alberta. These Caribou winter ranges are experiencing increasing pressure from resource extraction industries (forestry, energy sector) and concerns have been raised regarding increased Wolf predation pressure on Caribou in conjunction with landscape change. Thirty-one Wolves, from eight Wolf packs, were fitted with radiocollars on two Caribou winter ranges in the Rocky Mountain foothills, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Our 2003 and 2008 estimates are similar to the previously published estimates of 8,000 (Hayes and Gunson ) and 8,100 wolves (Theberge ), which were both based on expert opinion. Our estimated regional densities are within the range of those estimated for wolves using radio telemetry and snow‐tracking within small study areas in British Columbia (Hatter , Seip , Bergerud and Elliot , Hatler et al ) and similar to those reported from neighboring jurisdictions (Bjorge and Gunson , Hayes and Harestad , Hayes et al , Kuzyk et al , Webb et al ). Our estimated regional densities are also within the lower range of wolf densities from the western North America studies reported by Fuller et al ().…”
Section: Discussionsupporting
confidence: 84%
“…Our 2003 and 2008 estimates are similar to the previously published estimates of 8,000 (Hayes and Gunson ) and 8,100 wolves (Theberge ), which were both based on expert opinion. Our estimated regional densities are within the range of those estimated for wolves using radio telemetry and snow‐tracking within small study areas in British Columbia (Hatter , Seip , Bergerud and Elliot , Hatler et al ) and similar to those reported from neighboring jurisdictions (Bjorge and Gunson , Hayes and Harestad , Hayes et al , Kuzyk et al , Webb et al ). Our estimated regional densities are also within the lower range of wolf densities from the western North America studies reported by Fuller et al ().…”
Section: Discussionsupporting
confidence: 84%
“…The wolf–caribou dynamics in the central Arctic are different than those documented in other study areas where alternative prey occur at relatively high densities and can sustain wolves in the absence of abundant caribou (Ballard et al , ; Kuzyk et al ; Serrouya et al ; Hervieux et al ). For example, the home ranges of central Arctic wolves are amongst the largest in North America (Walton et al ).…”
Section: Discussionmentioning
confidence: 66%
“…In more productive systems like the foothills and boreal plains of Alberta and low‐elevation slopes of the Rocky Mountains of British Columbia, where evidence supporting DMAC has been reported, total ungulate biomass was much higher. Moose densities can be as high as 120–250 moose/1,000 km 2 (e.g., Little Smoky, Alberta, pre‐wolf removal [unpublished data cited in Kuzyk et al 2006]). But the alternate‐prey guild is also diverse, including populations of elk ( Cervus canadensis ), mule deer ( O. hemionus ), and white‐tailed deer.…”
Section: Discussionmentioning
confidence: 99%